Strategi Good Environment Pemerintah Kota Surabaya Pada Program Pembangkit Listrik Berbasis Sampah di TPA Benowo Kota Surabaya - Trigopala, Komang Yuda; Lail, Ramadhani Nurullah Addaru (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The waste management issue in Indonesia has become an urgent concern in recent years. With rapid population growth and urbanization, the volume of waste generated in the country continues to rise. Unfortunately, the waste management infrastructure remains insufficient, and public awareness regarding the importance of waste reduction, segregation, and recycling needs improvement. One of the main challenges in waste management in Surabaya is the limited infrastructure at the Benowo landfill. The lack of adequate final disposal sites (TPA) hinders the effective management of waste. This study aims to evaluate the strategies employed by the Surabaya city government in developing waste-to-energy power plants at the Benowo landfill. The research uses a qualitative descriptive approach and was conducted at the Benowo landfill and PT. Sumber Organik, the only landfill in Surabaya with a Waste-to-Energy Power Plant (PLTSa). Additionally, data was gathered through interviews, observations, and documentation at the Surabaya Environmental Agency. The results of the study indicate that the integration of the Benowo landfill and PT. Sumber Organik in the development of a waste-to-energy plant can provide significant economic, social, and environmental benefits.